KNOWLEDGE OF PRIMIGRAVIDA'S WOMEN TROUGHS PREGNANCY EXERCISE - Sriyatin S; Diah Martin (Journal of Maternity Care and Reproductive Health, 2018)
Pregnancy exercise is a physical exercise for pregnant women to prepare them physically or mentally to face childbirth. The number of ANC classes with pregnancy exercise programs was 76 classes in Cirebon City in 2015. The purpose of this study was to determine the knowledge of Primigravida women about pregnancy exercise. This research applied a descriptive method. The sample was chosen using purposive sampling technique. The number of samples is 37 pregnant women. The research location in Kalitanjung Community Health Center, Cirebon City. Respondents filled out questionnaires about knowledge related to pregnancy exercise. Data is analyzed by percentage, and presented in the form of a table. The results of the study showed that the knowledge level of primigravida women who had attended the pregnancy exercise class was good 7.1%, moderate 50%, and insufficient 42.9%. Whereas, primigravida women who have never had a pregnancy exercise class, 1.7% of them have a good knowledge, moderate 52.2%, and low 46.1%. Knowledge of primigravida women who have and have never attended classes for pregnant women varies, but most at the level of knowledge are at the moderate level. It is expected that pregnant women can add information about pregnancy exercise and increase their motivation to do pregnancy exercises so it would enhance pregnancy and infant's health.Keywords: knowledge, pregnancy exercise, primigravida